Brand Positioning Usaha Thrifting Den Market Pada Media Sosial Instagram @den.markett - Amalia, Shira Putri; Nur Aini Shofiya Asy'ari (Jurnal Ilmu Komunikasi, 2025)
The purpose of this study is to analyze how Den Market builds a strong brand image, differentiates itself from competitors, and attracts its target market through digital marketing strategies. The method used is descriptive qualitative, with data collected through interviews and content observation on the Instagram account @den.markett. The analysis refers to the Brand Positioning theory, which includes four indicators: (1) Product Attribute. (2) Price. (3) Product Quality. (4) Perceived Benefits. The results of the study show that the most dominant indicator is Product Attribute, where the uniqueness of content presentation and shopping experience on social media are the main attractions that differentiate Den Market from its competitors while strengthening the brand image in the minds of consumers